Effect of Three Parts of Moringa oleifera in the Control of Brown Blotch of Cowpea (Vigna unguiculata) L. WALP) - Zakari, B.G; Mark, W. A.; Chimbekujwo , I.B. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2023)
The study was carried out to investigate the effect of Moringa oleifera, at different concentrations levels to control Colletotrichum capsici, a pathogen of Brown blotch of cowpea in the Savannah. The study was carried out at the laboratory of the Department of Plant Science Modibbo Adama University Yola. C. capsici was isolated on unhealthy roots tissues of cowpea obtained from infected farm in Gombe State were cut off and surface sterilized by soaking in ethanol (75%, v/v) for 40 seconds then 4 min in hypochlorite (1%, v/v) and subsequently soaking in ethanol (75%, v/v) for 30 seconds again, to remove residual hypochlorite, finally rinsed in sterile distilled water, and blot-dried on clean sterile paper to remove sterilant. The pieces were transferred with a sterile tweezer, shaking off excess water onto a plate of PDA containing 2% potato dextrose agar containing streptomycin sulphate at 50 mg/l to prevent bacterial growth. Plates were then inoculated with various plant extracts of M. oleifera at concentrations of 2.00/ 10mls, 2.5/ 10mls, and 3.00/ 10mls of the medium for fungal growth. A mycelia disc of C.capsici was placed in the centre of the petri disc, to test the inhibitory activities of various control treatments. The mycelia growths on the petri dish were recorded three days, six days and nine days after inoculation. In vitro control trial was completely randomized design (CRD) with three replications. Data obtained were analysed, using analysis of variance (ANOVA) with Genstart. Version 14 Statistical Analysis System (SAS) (PC/Window) April 2023. Mean were separated at (p<0.05). Results from the experiment indicated that 3.00 ml of leaves and stem extracts of Moringa oleifera give the best control, suppressing the mycelial growth of the fungus to 1.63 cm, followed by stem back at 2.50 and 3.00 concentrations yielding mycelial growth of 1.67cm and 1.70 cm with 3.23 and 3.20 zones of inhibition respectively compare with 4.37 cm in the control experiment. Results from In-vitro experimental studies revealed that the best control effect was found in using 3.00 ml of stem extract of M. oleifera with the highest inhibition zone of 3.27 cm on the nine day after inoculation. It may be concluded from the results that the extracts used in this research are of potent antifungal activity against Colletotrichum capsici. Thus, should be explored further for fungal control activities and other uses as this is important in combating the recent observed emergence of drug resistance organisms.